Evaluating the processing of alum sludge as a pozzolanic material: A review - Izza Wajihah, Ismail; Rahimah, Embong; Al Biajawi, Mohammad I. (Polska Akademia Nauk, 2025)
Alum sludge (AS) is an inevitable by-product generated during water purification and wastewater treatment plant when aluminium salts are used during the coagulation process. The study primarily aimed at comprehensive review of the physical, chemical and microstructure properties of alum sludge, assessing its suitability to act as a pozzolanic material in cement as a partial replacement for ordinary cementitious materials. AS has been proven to have high amount of silicon dioxide (SiO2), iron oxide (Fe2O3) and aluminium oxide (Al2O3) from XRD analysis. Scanning Electron Microscopic (SEM) was conducted to fully understand the morphological structure of AS. Various analytical techniques are implemented to assess the pozzolanic potential of alum sludge. Comparative studies have highlighted the use of alum sludge in concrete which shows a favourable outcome in terms of the mechanical strength including compressive strength, flexural strength and durability. The findings in the present studies suggest that with a proper treatment and processing, alum sludge can be a viable and eco-friendly alternative to conventional pozzolanic materials. The future challenges of the process in the development of an effective alum sludge were discussed.